La fenomenología en arquitectura como estímulo en el proceso de sanación para la población víctima de abuso sexual. (2023)
The optimization of the spatial perception of psychological treatment arises through the incorporation of design guidelines to generate a stimulus in the recovery process of the population victim of sexual abuse, of which problems such as the deficiency of the services offered for the healing, the lack of concrete treatments for healing and scarcity of spaces for psychological treatment and recovery, focused on people with psychological traumas that include PTSD (post-traumatic stress disorder), anxiety, panic attacks, disorder of phobia and depression.